A Taxonomy of Selected High School Equivalency Materials. Reading Science Materials. Supplementary Inventory - New York State Education Dept., Albany. Bureau of General Education Curriculum Development; New York State Education Dept., Albany. Bureau of General Education Curriculum Development ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1976)
Instructors can use this inventory to prepare high school equivalency students for the reading skills test of the new form of the Test of General Educational Development (GED). It replaces the instrument previously recommended for that purpose, the Iowa Tests of Educational Development (ITED). Fifty-two multiple choice questions test the ability to interpret seventeen reading passages, illustrations, charts, or tables. An answer key and sheets for recording student responses are included. The skills needed to answer each question are identified, such as reading chemical formulas, inferring scientific generalizations, or identifying emphasis. After a student's responses are evaluated, the instructor should note any skill weaknesses and prescribe instruction using the designated card from the companion volume, A Taxonomy of Selected High School Equivalency Materials (Reading), ED 114 766. This Taxonomy is keyed to three New York State Education Department publications and six commercially available programs that can be used to introduce and reinforce specific skills which the student has not mastered. The materials range in difficulty from a seventh grade to a twelfth-fourteenth grade reading level. (CP)
ERIC Note: For related documents, see ED 114 766 and TM 008 126 ; Not available in hard copy due to marginal legibility of parts of document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; Diagnostic Tests; Equivalency Tests; High School Equivalency Programs; Natural Sciences; Reading Comprehension; Reading Skills; Science Tests; Scientific Literacy; Test Items; General Educational Development Tests; Tests/Questionnaires.